Relationship between PLR and Clinicopathological Characteristics of Patients with Advanced NSCLC and Its Predictive Value for the Efficacy of Chemotherapy and Prognosis - Jianming Zhao; Yiping Pan; Yu Sheng; Jun Sun (Emergency Medicine International)
Objective. To investigate the relationship between blood platelet-to-lymphocyte ratio (PLR) and clinicopathological characteristics of patients with advanced non-small cell lung cancer (NSCLC) and evaluate the value of PLR for predicting the efficacy of chemotherapy and prognosis. Methods. The clinical data of 175 patients with advanced NSCLC diagnosed from March 2017 to December 2018 in our hospital were retrospectively analyzed, and the data of 175 healthy subjects from our hospital physical examinations were included. The platelet was detected by using a blood cell analyzer to calculate PLR. According to the average PLR value (197) before chemotherapy, 175 patients were divided into the low PLR group (=78) and the high PLR group (=97). The relationship between the expression levels of PLR and clinicopathologic features was analyzed, and the Kaplan–Meier survival curve was used to analyze the relationship between the expression levels of PLR and prognosis. Results. The results showed that prechemotherapy PLR levels were significantly higher in NSCLC compared with the healthy subjects (P<0.05). After 4 cycles of chemotherapy, the PLR levels were significantly lower than those during prechemotherapy (P<0.05). The proportion of TNM (IV) stage cases in the low PLR group was lower than that in the high PLR group (P<0.05). The total effective rate of the first-line chemotherapy was 46.9% (82/175). The effective rate of IIIb staging was higher than that in IV staging (P<0.05), and the effective rate of the low PLR group was higher than that in the high PLR group (P<0.05). Multivariate logistic analysis showed that TNM stage 4 and high PLR level were the independent risk factors for the efficacy of the first-line chemotherapy in patients with advanced NSCLC (P<0.05), and the high PLR level was an independent risk factor affecting the prognosis of patients with advanced NSCLC. The median overall survival (OS) of patients with the low PLR group was 20.8 months, higher than the 12.0 months of patients with the high PLR group (P<0.05). Conclusion. PLR might have a certain clinical significance for predicting the TNM staging of NSCLC and can provide important diagnostic and prognostic results for patients.